Negotiating Digital Risks: The Roles of Parents and Islamic Education Teachers in Protecting Students from the Negative Impacts of Technology - Arwanti Arwanti; Desi Harmanabila; Nurfadillah Rezky; Ainun Mutia (Postgraduate Program of the State Islamic Institute of Palopo, 2025)
The rapid advancement of digital technology has significantly transformed students’ learning environments and social interactions, creating both opportunities and challenges in contemporary education. While digital technology offers substantial benefits for communication and learning, its uncontrolled use also exposes students to various risks, including excessive smartphone dependency, reduced academic focus, social media addiction, exposure to harmful online content, and behavioral changes. This study aims to examine the roles of parents and Islamic Education (PAI) teachers in protecting students from the negative impacts of technology at SMP Negeri 4 Ponrang, Indonesia, and to identify the supporting and inhibiting factors influencing these efforts. This study employed a qualitative approach using a case study design. Data were collected through observations, semi-structured interviews, and documentation involving parents, Islamic Education teachers, and students. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing. The findings reveal that parents function as primary digital gatekeepers through supervision, communication, guidance, and moral education. Meanwhile, Islamic Education teachers serve as moral guardians by strengthening students’ ethical awareness through religious instruction, behavioral supervision, and counseling. The study also found that effective digital risk prevention requires strong collaboration between family and school. Supporting factors include students’ self-awareness, family support, positive social environments, and teacher involvement, while inhibiting factors include rapid technological development, easy internet access, environmental influence, and limited parental supervision. This study highlights the importance of integrating digital literacy, digital ethics, and Islamic character education to strengthen students’ moral resilience in navigating contemporary digital challenges.